2020
DOI: 10.3390/ijms21020638
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Modifications in the Porcine Intramuscular Adipocytes during Differentiation and Exogenous Stimulation with TNF-α and Serotonin

Abstract: Adipocytes are dynamic cells that have critical functions to maintain body energy homeostasis. Adipocyte physiology is affected by the adipogenic differentiation, cell program, as well as by the exogenous stimulation of biochemical factors, such as serotonin and TNF-α. In this work, we investigated the global transcriptome modifications when porcine intramuscular preadipocyte (PIP) was differentiated into porcine mature adipocyte (pMA). Moreover, we studied transcriptome changes in pMA after stimulation with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Specifically, the serotonin 1E receptor gene ( htr1e ) has been linked with feed intake in rainbow trout ( Callet et al, 2018 ) and in rats ( Hayes and Covasa, 2006 ). A recent study in pigs reported that intramuscular adipocytes showed dose-dependent serotonin stimulation, which then resulted in decreased fat accumulation in mature adipocytes ( Tada et al, 2020 ). A GWAS in sheep linked a SNP close to htr1e with internal fat content ( Hernández-Montiel et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the serotonin 1E receptor gene ( htr1e ) has been linked with feed intake in rainbow trout ( Callet et al, 2018 ) and in rats ( Hayes and Covasa, 2006 ). A recent study in pigs reported that intramuscular adipocytes showed dose-dependent serotonin stimulation, which then resulted in decreased fat accumulation in mature adipocytes ( Tada et al, 2020 ). A GWAS in sheep linked a SNP close to htr1e with internal fat content ( Hernández-Montiel et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…RPL11 has been revealed to play a role in fat storage [36]. SRC and STAT3 can respond to adipogenesis through the TNF-α pathway [37]. We inferred that PELP1 may in uence IMF by interacting with other proteins.…”
Section: Discussionmentioning
confidence: 90%
“…Unlike the microorganism derived MAPMs which induce a rapid onset of proinflammatory reaction, DAMPs are endogenous molecules (e.g., free fatty acids, cholesterol, ceramides) derived from dead adipocytes, which can lead to a non-infectious chronic inflammation [ 37 , 38 , 39 ]. In our previous study, we have demonstrated the MAMPs-mediated acute inflammatory responses in adipocytes using a short-term differentiation period (4 days) of PIP cells [ 17 , 26 , 30 ]. However, like other standard in vitro adipocytes models, our previous approaches have the limitation of not able to address the mechanisms of sustained inflammation because of the short period of adipocytes culture.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies suggested that TNF-α affects glucose homeostasis and fat accumulation in adipocytes, as well as their differentiation (reviewed in ref [ 29 ]). We have also demonstrated that TNF-α stimulation significantly affect the biology of PIP cells during in vitro differentiation for a period of four days [ 17 , 30 ].…”
Section: Introductionmentioning
confidence: 99%